2020
DOI: 10.1177/1750458920928843
|View full text |Cite
|
Sign up to set email alerts
|

Overview of multimodal analgesia initiated in the perioperative setting

Abstract: Despite progress in pain management in the perioperative setting, the literature is full of evidence that managing postoperative pain is suboptimal. Since the mechanism of pain is complex, the use of multimodal technique allows clinicians to use a combination of two or more drugs targeting different areas of pain transmission because of surgery. As part of enhanced recovery initiatives after surgery, healthcare and professional organisations incorporate the use of multimodal analgesia in surgical guidelines to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…The impact of MMA in reducing opioid consumption, decreasing adverse effects, and improving postoperative recovery is well documented in the literature [1,9,16]. A variety of MMA protocols with or without the addition of regional anesthesia techniques have been studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of MMA in reducing opioid consumption, decreasing adverse effects, and improving postoperative recovery is well documented in the literature [1,9,16]. A variety of MMA protocols with or without the addition of regional anesthesia techniques have been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative anxiety, catastrophizing and decreased response to conditioned pain modulation have been identified as risk factors for patients likely to experience persistent, uncontrolled postoperative pain. Patients receiving preoperative education have less anxiety, lower pain scores, reduced hospital LOS, and a faster return to their baseline [9,19]. Thus, it is recommended that patients receive preoperative counseling to help establish appropriate expectations for postoperative pain and proper management [9,19,26,32].…”
Section: Next Stepsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to EA, abortive medications, intravenous medications, peripheral nerve blocks, and other methods of postoperative pain management are widely used. Multi-model analgesia, which compensates for the shortcomings of each analgesic method rather than providing pain management in isolation, is essential (Tubog 2021). Previous studies have reported that postoperative analgesia with EA for RRP prolongs the length of hospital stay (Mir et al 2013).…”
Section: Accepted Manuscript 14mentioning
confidence: 99%
“…Hal tersebut dapat mengurangi dosis obat yang diberikan, termasuk dosis opioid dan dapat mengurangi efek samping yang muncul. 7 Dokumentasi pada manajemen nyeri pascaoperasi juga merupakan salah satu langkah penting dalam pelayanan manajemen nyeri. Rekam medis tersebut memberikan informasi penting bagi tim tenaga kesehatan untuk memberikan manajemen nyeri.…”
Section: Pendahuluanunclassified